Differentiation of soil metabolic function and microbial communities between plantations and natural reforestation - Zhang, Nannan; Chen, Xiaoxia; Ren, Tingju; Luo, Jiangcheng; Liang, Jin; Wang, En Tao; Shi, Fusun (Frontiers in Microbiology, 2025)
Reforestation plays a vital role in restoring the soil degradation areas. However, the mechanisms by which different restoration approaches affect the soil properties and microbial communities remain unclear. Aiming to understand the interactions between plant species, soil properties, and microbial communities in different restoration approaches, we investigated the soil microbial community using nontargeted metabolomics to explore how the reforestation approach affects soil physicochemical properties, soil metabolites, and soil microbial communities. The results showed that the reforestation approach, soil layer, and their interactive effects significantly affected soil organic carbon, total nitrogen, dissolved organic carbon, available phosphorus concentrations, and root traits. The diversity and composition of bacterial and fungal communities in natural reforestation (NR) were different from those in artificial mono-plantations, and their network interactions were more significant in NR than in artificial plantations. A clear separation of metabolites between the artificial plantations and NR was observed in the soil metabolite analysis. Two pathways, linoleic acid metabolism, and valine, leucine, and isoleucine biosynthesis, were significantly regulated between the artificial mono-plantations and NR. Different soil traits were significantly correlated with dominant microbial taxa in the four reforestation approaches. 13-L-hydroperoxylinoleic acid, 13-S-hydroxyoctadecadienoic acid, homovanillin, and 9,10-epoxyoctadecenoic acid showed the highest correlation with the microbial taxa in the network. Partial least squares path modeling (PLS-PM) shows that root-mediated soil physicochemical properties were the primary factors affecting the bacterial community among the reforestation approaches. The soil fungal community is directly regulated by plant roots in the subsoil and indirectly regulated by the root-mediated physicochemical properties in the topsoil. We conclude that different reforestation approaches affect the soil microbial community through root and soil physicochemical properties rather than soil metabolites.